Stent length and -diameter and long-term clinical outcomes following percutaneous coronary intervention with drug-eluting stent implantation. (3rd October 2022) - Van Hemert, N; Stella, P R; Rozemeijer, R; Kraaijeveld, A O; Rittersma, S Z; Leenders, G E H; Stein, M; Frambach, P; Van Der Harst, P; Agostoni, P; Voskuil, M
Abstract: Background: Long total stent length and small stent diameter have been associated with adverse events following percutaneous coronary intervention (PCI). Purpose: To assess whether stent length and -diameter influence long-term target-lesion failure (TLF) following implantation of contemporary drug-eluting stents (DES) in an all-comers population undergoing PCI. Methods: Patients included in the ReCre8 trial were stratified for troponin status and diabetes and randomized to implantation of a permanent polymer (PP-ZES) or polymer-free stent (PF-AES). Troponin negative patients were treated with dual antiplatelet therapy for one month, and troponin positive patients for twelve months. For the analysis on stent length, patients were divided in the quartiles of total stent length implanted per patient. Group 1a had a stent length of ≤18mm, Group 2a had a total stent length between 18 and 30mm, Group 3a had a total stent length of ≥30mm and lower than 49mm, and Group 4a had a total stent length of 49mm or more. For the analysis on stent diameter, patients were divided in the quartiles of the smallest stent diameter implanted per patient. Group 1b had a minimal stent diameter of ≤2.5mm, Group 2b had a minimal stent diameter between 2.5 and 3mm, Group 3b had a minimal stent diameter of ≥3mm and lower than 3.5mm, and Group 4b had a minimal stent diameter of 3.5mm or higher. The primary endpoint of TLF and its components – cardiac death, target-vessel myocardial infarction and target-lesion revascularization (TLR) – were assessed after three years. Results: After division of patients in subgroups based on stent length, Group 1a included 409 patients (27.6%), Group 2a included 322 patients (20.7%), Group 3a included 376 patients (25.3%) and Group 4a included 377 patients (25.4%). After three years, TLF occurred more frequently in Group 4a with 6.6% in Group 1a, 8.4% in Group 2a, 7.7% in Group 3a and 18.0% in Group 4a (p<0.001) as shown in Figure 1. This was driven by a higher rate of TLR (p<0.001) and target-vessel myocardial infarction (p<0.001) in Group 4a. After division of patients in subgroups based on stent diameter, Group 1b included 408 patients (27.5%), Group 2b included 214 patients (14.4%), Group 3b included 477 patients (32.1%) and Group 4b included 386 patients (26.0%). After three years, TLF occurred more frequently in Group 1b with 14.0% vs. 7.9% in Group 2b, 8.6% in Group 3b and 9.3% in Group 4b (p=0.0241) as shown in Figure 2. The difference in TLF was driven by a higher rate of TLR in Group 1b (8.6% vs. 3.7% vs. 4.4% vs. 4.9%; p=0.016). Conclusion: In an all-comers population undergoing PCI with implantation of contemporary DES, a stent length ≥49mm and a stent diameter ≤2.5mm were associated with a higher rate of TLF after three years. Funding Acknowledgement: Type of funding sources: None.